2017
DOI: 10.1103/physrevb.95.155416
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field evolution of spin blockade in Ge/Si nanowire double quantum dots

Abstract: We perform transport measurements on double quantum dots defined in Ge/Si core/shell nanowires and focus on Pauli spin blockade in the regime where tens of holes occupy each dot. We identify spin blockade through the magnetic field dependence of leakage current. We find both a dip and a peak in the leakage current at zero field. We analyze this behavior in terms of the quantum dot parameters such as coupling to the leads, interdot tunnel coupling as well as spin-orbit interaction. We find a lower bound for spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…In order to realize a spin 3/2 qubit in the DQD devices we rely on PSB as a spin-selective read-out mechanism 25 , 26 . PSB occurs in a (1, 1) → (2, 0) or an equivalent (2N−1, 2N−1) → (2 N, 2N−2) charge configuration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to realize a spin 3/2 qubit in the DQD devices we rely on PSB as a spin-selective read-out mechanism 25 , 26 . PSB occurs in a (1, 1) → (2, 0) or an equivalent (2N−1, 2N−1) → (2 N, 2N−2) charge configuration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This large anisotropy follows from an almost vanishing g-factor (g * min = 0.2) along the NW axis. Pauli spin blockade can elucidate the spin-flip mechanisms through the behaviour of the leakage current as a function of magnetic field 193,199,200 .…”
Section: Nanowiresmentioning
confidence: 99%
“…Since double quantum dot (DQD) configurations provide a versatile platform for the implementation of quantum information processing [10,11], such systems have also been considered in hybrid setups involving superconducting elements. Experimentally, their bound states have been probed by the tunneling spectroscopy, using InAs [12][13][14][15][16][17], InSb [18], Ge/Si [19] quantum dots or carbon nanotubes [20,21] contacted with superconducting lead(s), as well as by the scanning tunneling microscopy (STM) applied to the magnetic dimers deposited on su-perconducting substrates [6,[22][23][24]. The single V, Cr, Mn, Fe, and Co atoms deposited on aluminum have revealed that Cr and Mn atoms have contributions from different orbitals to subgap quasiparticles, whereas the other elements merely consist of one pair of the in-gap bound states [25].…”
Section: Introductionmentioning
confidence: 99%